The Future of the Nuclear Industry Reconsidered : Risks, Uncertainties, and Continued Potential - Kessides, Ioannis N. (World Bank, Washington, DC, 2014)
Skeptics point out, with some justification, that the nuclear industry's prospects were dimmed by escalating costs long before Fukushima. If history is any guide, one direct consequence of the calamity in Japan will be more stringent safety requirements and regulatory delays that will inevitably increase the costs of nuclear power and further undermine its economic viability. For nuclear power to play a major role in meeting the future global energy needs and mitigating the threat of climate change, the hazards of another Fukushima and the construction delays and costs escalation that have plagued the industry will have to be substantially reduced. One promising direction for nuclear development might be to downsize reactors from the gigawatt scale to less-complex smaller units that are more affordable. Small modular reactors (SMRs) are scalable nuclear power plant designs that promise to reduce investment risks through incremental capacity expansion; become more standardized and reduce costs through accelerated learning effects; and address concerns about catastrophic events, since they contain substantially smaller radioactive inventory. Given their lower capital requirements and small size, which makes them suitable for small electric grids, SMRs can more effectively address the energy needs of small developing countries.